Stable isotopes in guano: Potential contributions towards palaeoenvironmental reconstruction in Tabon Cave, Palawan, Philippines. (19th September 2016) - Choa, O.; Lebon, M.; Gallet, X.; Dizon, E.; Ronquillo, W.; Jago-on, S.C.; Détroit, F.; Falguères, C.; Ghaleb, B.; Sémah, F.
Abstract: Tabon Cave is a key site for the understanding of modern human dispersals in the Philippine archipelago and Island Southeast Asia. Nestled in the karst landscape that borders the southwestern coast of Palawan, it has delivered the earliest confirmed Homo sapiens remains in the Philippines dating to the late Pleistocene, as far back as around 47 ka. Among other methods, the broad characteristics of the environment in which these humans once lived may be drawn using stable isotope analysis of the rich guano deposits in the cave, an approach that follows a growing number of studies indicating the potential of guano as a palaeoenvironmental archive. δ 13 C values reveal the general prevalence of C3 forest tempered by savannah woodland with grassland contributions both well before and slightly after a securely-dated fireplace at 32 ka; the lower interval would refer to OIS 3 or older interglacial periods, while the upper interval would refer to the transition either before or after the Last Glacial Maximum. No useful conclusions are drawn from δ 15 N results due to suspected ammonia fractionation. Pending future dating efforts for confirmation, this preliminary study contributes to the development of an alternative and promising palaeoenvironmental proxy and hopes to shed further light on the prehistoric odysseys that took place across Island Southeast Asia.